The Impact of Covid-19 on Domestic Violence: A Study of Khyber Pakhtunkhwa - Ali, Sheraz; Khan, Saeeda; Khan, Awais Alam; Khan , Muhammad Asghar (Pakistan Journal of Humanities and Social Sciences, 2023)
This research study focuses on the impact of Covid-19 on domestic violence in Khyber Pakhtunkhwa. The target population of this research study was the number of local households of Khyber Pakhtunkhwa. The data was collected from the local households in six districts including Swat, Mardan, Swabi, Charsadda, Peshawar and Nowshera. From six districts of Khyber Pakhtunkhwa, 300 samples were collected. From each district 50 samples were collected including 25 females and 25 males. All the samples were randomly selected. The data was manually collected in the form of a pre-tested questionnaire. Domestic violence was measured by Conflict Tactics Scale. The results revealed that Covid-19 lock down was a painful situation that increased frustration among the people when coupled with economic uncertainty resulted in domestic violence. Factors that highly contributed to domestic violence during Covid-19 lock down included social isolation, frustration, stress and anxiety. The results did not support the null hypothesis; hence, the alternative hypothesis was accepted. From the findings it was identified that human stress caused by restrictions on social mobility and social engagements resulted in domestic violence and this factor was comparatively stronger.